A proposal for selective resuscitation of adult cardiac arrest patients in a pandemic - Antony Hsu; William Weber; Alan Heins; Elaine Josephson; Robert Kornberg; Rosemarie Diaz (Journal of the American College of Emergency Physicians Open)
Abstract Allocation of limited resources in pandemics begs for ethical guidance. The issue of ventilator allocation in pandemics has been reviewed by many medical ethicists, but as localities activate crisis standards of care, and health care workers are infected from patient exposure, the decision to pursue cardiopulmonary resuscitation (CPR) must also be examined to better balance the increased risks to healthcare personnel with the very low resuscitation rates of patients infected with coronavirus disease 2019 (COVID‐19). A crisis standard of care that is equitable, transparent, and mindful of both human and physical resources will lessen the impact on society in this era of COVID‐19. This paper builds on previous work of ventilator allocation in pandemic crises to propose a literature‐based, justice‐informed ethical framework for selecting treatment options for CPR. The pandemic affects regions differently over time, so these suggested guidelines may require adaptation to local practice variations.